Dynamics of pulmonary venous flow in fetuses with intrauterine growth restriction. (29th December 2014) - Bravo‐Valenzuela, Nathalie J. M.; Zielinsky, Paulo; Huhta, James C.; Acacio, Gregório L.; Nicoloso, Luiz H.; Piccoli, Antonio; Busato, Stefano; Klein, Caroline
Abstract Objective To test the hypothesis that the pulmonary vein pulsatility index (PVPI) is higher in fetuses with growth restriction (IUGR) than in normal fetuses. Methods Twenty‐two fetuses with IUGR and twenty‐one (21) fetuses with appropriate growth for gestational age from healthy mothers were studied. PVPI was calculated by Doppler echocardiography [maximal velocity (systolic or diastolic peak) − pre‐systolic peak / mean velocity]. Obstetric ultrasound was used to assess fetal biometry and Doppler to assess the uterine, umbilical and middle cerebral arteries PI. Statistical analysis used t test and Pearson's correlation. Results Mean gestational age was 31.5 +/− 2.1 weeks in the control group and 31.4 +/− 3.1 weeks in IUGR (P = 0.91). The PI of uterine and umbilical arteries were higher in IUGR than in controls (P < 0.001). Mean PVPI in IUGR fetuses was 1.31 +/− 0.41, and in controls it was 0.83 +/− 0.11 (P < 0.001). Conclusion The pulsatility index of pulmonary venous flow in fetuses with growth restriction is higher than in normal fetuses, probably as a result of left atrial dynamics alteration secondary or not to fetal left ventricular diastolic dysfunction. © 2014 John Wiley & Sons, Ltd.